2007 IEEE 13th International Symposium on High Performance Computer Architecture 2007
DOI: 10.1109/hpca.2007.346183
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Device Timing Variability on Full Chip Timing

Abstract: As process technologies continue to scale, the magnitude of within-die device parameter variations is expected to increase and may lead to significant timing variability. This paper presents a quantitative evaluation of how low level device timing variations impact the timing at the functional block level. We evaluate two types of timing variations: random and systematic variations. The study introduces random and systematic timing variations to several functional blocks in Intel® Core™ Duo microprocessor desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…circuit-level techniques must be applied carefully to all the critical executions paths for timing violations. Annavaram et al showed that the distribution of timing margins for different paths across functional blocks in the Intel Core Duo microprocessor have hundreds of paths within 10% timing margins [5]. Designs such as Razor impact overall processor performance and area overhead, as well as design and verification effort.…”
Section: Discussionmentioning
confidence: 99%
“…circuit-level techniques must be applied carefully to all the critical executions paths for timing violations. Annavaram et al showed that the distribution of timing margins for different paths across functional blocks in the Intel Core Duo microprocessor have hundreds of paths within 10% timing margins [5]. Designs such as Razor impact overall processor performance and area overhead, as well as design and verification effort.…”
Section: Discussionmentioning
confidence: 99%
“…However, Razor may be costly to implement in a high-performance out-of-order core with several large array structures and tight timing paths. A recent study by Annavaram et al [3] shows the distribution of timing margins for different paths across functional blocks in the Intel Core Duo microprocessor have hundreds of paths within 10% timing margins. This suggests that voltage-induced violations are likely to affect many paths.…”
Section: Related Workmentioning
confidence: 99%